O lúdico na Física: explicando a Física por meio de super-heróis - Feitosa, Lindonjonson Souza (2021)
Finding the appropriate methodology in the teaching and learning process is a great challenge for teachers today and when it comes to the subject of Physics, this challenge becomes even greater in the face of the huge rejection that most students have for this subject, either by involve theory associated with calculations or even for relating subjects in the same question. This work aims to bring a pedagogical proposal based on Gardner's theory of multiple intelligences, through playfulness. To this end, a subject that is part of the universe of the students and that pleases them, the universe of the characters of comics and cinema, was approached. The idea is to use such characters so that students can relate the physical aspects inherent to each one, making physical knowledge better used and less rejected by the student in the face of something that is pleasant and pleasurable. The methodology used was divided into two parts, in the first the students made presentations, where they explained topics such as kinematics, dynamics, fluids and electricity. Among the various themes chosen, some, on purpose, had not yet been explored by the teacher in the classroom. The second part aims to contribute to the product of this project and at the same time measure what remains of the presentations in relation to the conceptual knowledge of physics and the characters. For the presentations, the students had to elaborate questions in which the theme was the characters combined with the physical concepts and these questions will be part of a book, an educational product, only with questions related to the theme of this project. At the end of the process, it was realized that through the presentations and questions made by the students, knowledge about physics was better accepted and understood by the vast majority of the class.